Fractal‐Theory‐Based Control of the Shape and Quality of CVD‐Grown 2D Materials. Issue 35 (2nd July 2019) - Li, Junzhu; Chen, Mingguang; Zhang, Chenhui; Dong, Haocong; Lin, Weiyi; Zhuang, Pingping; Wen, Yan; Tian, Bo; Cai, Weiwei; Zhang, Xixiang
Abstract: The precise control of the shape and quality of 2D materials during chemical vapor deposition (CVD) processes remains a challenging task, due to a lack of understanding of their underlying growth mechanisms. The existence of a fractal‐growth‐based mechanism in the CVD synthesis of several 2D materials is revealed, to which a modified traditional fractal theory is applied in order to build a 2D diffusion‐limited aggregation (2D‐DLA) model based on an atomic‐scale growth mechanism. The strength of this model is validated by the perfect correlation between theoretically simulated data, predicted by 2D‐DLA, and experimental results obtained from the CVD synthesis of graphene, hexagonal boron nitride, and transition metal dichalcogenides. By applying the 2D‐DLA model, it is also discovered that the single‐domain net growth rate (SD‐NGR) plays a crucial factor in governing the shape and quality of 2D‐material crystals. By carefully tuning SD‐NGR, various fractal‐morphology high‐quality single‐crystal 2D materials are synthesized, achieving, for the first time, the precise control of 2D‐material CVD growth. This work lays the theoretical foundation for the precise adjustment of the morphologies and physical properties of 2D materials, which is essential to the use of fractal‐shaped nanomaterials for the fabrication of new‐generation neural‐network nanodevices. Abstract : The existence of a fractal‐growth‐based mechanism in 2D‐material chemical vapor deposition (CVD) synthesis is revealed. Based on fractal theory and CVD‐grown mechanisms, a 2D diffusion‐limited aggregation model is built up. Perfect correlations between theoretically simulated data and CVD experimental results are obtained. Precise control of 2D‐material shape and quality is achieved by adjusting single‐domain net growth rates in the CVD‐growth process.